A new horology data for Silene paeoniensis Bornm. in the flora of Republic of Macedonia - Matevski, Vlado; Sekovski, Živko; Kostadinovski, Mitko (Macedonian Journal of Ecology and Environment, 1994)
In this paper a new horology data for the endemic species Silene paeoniensis Bornm. (Caryophyllaceae) are presented. Its distribution on the territory of the Republic of Macedonia is limitet only in the canyon of the river Babuna and in Mariovo – the canyon of the river Crna Reka, Gradeshnica and river Satoka.